2012
DOI: 10.1027/0227-5910/a000112
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Suicide Letters in Turkey From a Cognitive Perspective

Abstract: These negative cognitions should be taken into consideration when therapeutic interventions are planned on individuals with suicidal thoughts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Conversely, most decedents who used suffocation as the mechanism for their death left an E-note. This is supported by other studies that hypothesized that the more opportunistic forms of suicide are less likely to result in leaving behind a suicide note (Heim & Lester, 1990;Ho et al, 1998;Kuwabara et al, 2006) as they required less planning.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Conversely, most decedents who used suffocation as the mechanism for their death left an E-note. This is supported by other studies that hypothesized that the more opportunistic forms of suicide are less likely to result in leaving behind a suicide note (Heim & Lester, 1990;Ho et al, 1998;Kuwabara et al, 2006) as they required less planning.…”
Section: Discussionsupporting
confidence: 70%
“…Studies that included in their analyses psychiatric histories and psychiatric hospitalizations reported contradictory findings. Several international studies reported that suicide decedents who had known mental health issues such as mental disorder, history of self-harm, or recent or prior psychiatric hospitalization were less likely to leave behind a note (Carpenter et al, 2016;Chia, Chia, & Tai, 2008;Demirel, Akar, Sayin, Candansayar, & Leenaars, 2008;Ho et al, 1998;Howard & Surtees, 2016;Kuwabara et al, 2006;Paraschakis et al, 2012;Salib et al, 2002;Wong, Yeung, Chan, Yip, & Tang, 2009). Stack and Rockett (2016), in their analysis of US data from the National Violent Death Reporting System, found that those with current mental health issues or depression were more likely to have left a suicide note (OR = 1.11 & OR = 1.22, respectively); however, those with current mental health treatment and alcohol abuse-related problems (15% and 24%, respectively) were less likely to have left a note.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to another study from Turkey that evaluated suicide notes, economic problems and relationship problems were the most common reason for suicide in males and females, respectively. 40,41 Oner et al 1 reported that the main reason for suicide in males between 1990 and 2000 was illness; in the present study, economic problems was the reason for suicide that showed the greatest significant between-sex difference. Previous studies have suggested that having a job can help alleviate the risk of suicide, especially for young males.…”
Section: Discussionmentioning
confidence: 53%
“…We also suggest that alcohol may influence the act of leaving a suicide note in males since it may be part of the process of suicidality. Nevertheless, other variables may also have a direct influence on this act such as personality features (41), specific cognitive distortions about the self, the world and the future each subject experienced during the suicidal process (50); these variables were not assessed in the present study and should be included in future studies.…”
Section: Discussionmentioning
confidence: 99%